IMPROVING LEARNING PROCESS AND STUDENT RESULTS LEARNING TO TUNE-UPMOTORCYCLE USING DEMONSTRATION METHODOF CLASS XI SMA N 1 PLAYEN YEAR STUDY2013/2014 - Haryono Haryono; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2014)
This research is to improve the learning process and results in learning a tune-up motorcycle using the demonstrationmethod of class XI SMA 1 Playen. This research is a classroom action research (PTK), using the demonstration method.Subyek this study were students of class XI SMA Negeri 1 Playen.Theimplementationofthisstudyusing3cycles,there is a (planning), implementation (actuating), observation (observing), and reflection (reflecting). Collecting data in this study are observations of student learning process and student learning outcomes test data pre-test, postesI, II, III and documentation as a support to the two data. Further observation data based on the observation of student learning just learning the positive process of learning student and test data were analyzed for comparison. Indicators of success in this classroom action research that student learning increases towards positive along with the use of methods of demonstration, is to see an increase from the pre-cycle to end the first cycle, the first cycle to the second cycle and the secondcyclebycycle III. From the results of this study concluded that the method could improve the demonstration of positive student learning, from the first cycle of 30%, 50% second cycle and third cycle of 80%. Learning is also more effective with students indicated more quickly adapt as a positive activity, especially in terms of increased student asked, noting the test and work on the problems. Demonstration method can improve the learning outcomes students of class XI SMA 1 Playen as evidenced by an increase in the average yield final test first cycle of 64.09; second cycle of 77.82 and 78.86 for the third cycle. So it proved with the increasing positive student learning canalso improve student learning outcomes.